Identificação e mapeamento de unidades geoambientais : uma contribuição ao planejamento territorial periurbano e à conservação dos recursos hídricos de Cuiabá, Mato Grosso - Figueredo, Rosamaria Rosan Dias (2018)
In the search for the sustainable use of the lands that are susceptible to urban occupation it is of the outmost importance to identify landscapes components on detailed scale due their critical role for territorial planning. Based on morpho-pedological mapping in a scale compatible with 1:25,000, it was possible to identify five geoenvironmental units: Hills (R1), Tabular Surfaces (R2), Straight Ramps (E1), Valleys (E2) and Swamps (D1). The units were defined by analyzing the Digital Elevation Model TOPODATA, integrated with optical remote sensing images and field surveyor. The morphopedological compartments that provided the conceptual model for the geoenvironmental units were also integrated with previous cartographic, geomorphological and geological data. These characteristics indicated the “natural vocation” for each unity, which was mainly defined in terms of their contribution for conserving natural resources and support for urban settlement projects. This study recommends the rigid environmental control of the studied area as it is upstream to the major watershed that drain the urban area of the Cuiaba City. It is also recommended to keep the density of occupation as low as possible, to recover the degraded areas and to preserve the identified sites that are still unaltered by human occupation.